PENGEMBANGAN MODUL PRAKTIKUM GENETIKA BERBASIS KETERAMPILAN PROSES SAINS UNTUK MAHASISWA PROGRAM STUDI PENDIDIKAN BIOLOGI - Etty Nurmala Fadillah; Erni Angraini (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2018)
The development of this practicum module is based on overcoming student difficulties in practicum implementation and final report making. Skillsbased modules of the science process to practice the skills of the process of science are observing, grouping, interpreting, predicting, formulating hypotheses, planning experiments, and communicating. This module is expected to lead the students to be actively involved in carrying out practicum activities independently related to the concept of the material to be studied. The purpose of this research is to produce teaching material product in the form of practical genetic module based on skill of science process that is feasible and practical used by students in genetic lecturing. Procedure of development in this research with 4-D model proposed by Thiagarajan that is define (definition), design (design), develop (development), and disseminate (dissemination). Data collection instruments used in the form of interviews and assessment questionnaire. Data analysis techniques used qualitative analysis by calculating the average score of each component of the module assessment and calculating practicality data on the use of the practicum module. The science-based genetic module of the science process module is appropriate for use by professors of materials experts, media experts, and linguists. Second, module practicum based on science skill based on students' responses have practicality in practicum practice that is 76,05% module contents, 76,26% presentation, and 76,10% from language.